Monitoramento da exposição pessoal ao poluente atmosférico black carbon - Carvalho, Amanda Maria (2017)
The concentration of atmospheric pollutants has been significantly growing over the last years, mainly due to anthropic sources, reducing the urban air quality and exposing the population to high pollution levels. The present study assesses the personal exposure to black carbon (BC) of couples in which both participants live in the same house and have different work routines. BC is a short-lived climate pollutant emitted by the incomplete combustion of carbonaceous materials, being harmful to both health and climate. The sampling campaign was conducted in Londrina, a mid-sized city in the Northern part of Paraná state, with six non-smoking couples that continuously carried portable BC monitors for 48 hours. Besides, two instruments simultaneously measured BC at the volunteers' home and at the campus of the Federal Technological University of Paraná (UTFPR), located in the city outskirts. The data sampled by the volunteers were classified into 4 microenvironments: home, work, transport and others. The results show a large variability of the dose and exposure values among the six sampled couples. It was also found that data from the fixed monitoring stations cannot accurately capture the high spatial variability of BC concentrations and therefore underestimate the dose values and individual exposure when compared to data collected with portable samplers. The location of the residence and the high BC concentrations at home can contribute to higher average exposure values. High BC concentrations were observed for volunteers working at UTFPR due to emissions from local biomass and waste burning, leading to exposure values of 1.38 μg m-3. In the category others, the highest concentrations occurred with the woman of the couple 1, during her trip to the supermarket with a mean exposure of 3.13 μg m-3, and for the man of the couple 6 when he was in the gym, with an average exposure of 1.52 μg m-3. The highest concentrations were found in the transport category, reaching maximum levels on the buses (54.16 µg m-3), followed by those monitored in the cars (50.70 µg m-3) and when walking (47.13 µg m-3). The highest exposure was found for the man in couple 1 who used the car as transportation mode, with a mean exposure of 8.35 µg m-3. The second highest exposure occurred with the man in couple 2, who used buses, with a mean exposure of 8.25 µg m-3. The exposure values observed during the motorized transport were higher than those found in the walking category. Furthermore, the average exposure was 3 times higher and the dose 4 times higher when the car windows were open than when the windows were closed. The results of this study show that although a couple spends an average of 10 hours per day in a common environment, the routine of each individual in different environments during the rest of the day can lead to large difference in exposure and dose values. This study also shows that to obtain more accurate exposure and dose values it is necessary to use data from portable samplers. However, it is suggested that the sample of volunteers should be larger so that the results are representative of the population.